PENERAPAN MODEL PROBLEM BASED LEARNING DIINTEGRASIKAN DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII - Hutagaol, Miranda; Imelda Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve students' mathematical problem-solving skills through the Problem-Based Learning (PBL) model integrated with a Culturally Responsive Teaching (CRT) approach. This study is a classroom action research with subjects from the 8th grade class VIII-3 of SMP Negeri 9 Medan for the 2024/2025 academic year. The results show an improvement in mathematical problem-solving skills: the indicator of performing problem-solving increased from 68.75 to 81.77. Additionally, the indicator of reviewing also showed an increase from 44.53 to 77.34. Overall, the average mathematical problem-solving ability of the students improved from 68.75 to 84.18, with a classical completeness of 93.75%. The N-gain achieved in cycle I was 0.49, which falls into the moderate category. Since the test results for students' problem-solving abilities and the teacher's activity results met the success indicators, the actions were not continued and were stopped at cycle II.